Human staff vs. service robot vs. fellow customer: Does it matter who helps your customer following a service failure incident?. (May 2020) - Ho, Ting Hin; Tojib, Dewi; Tsarenko, Yelena
Highlights: Customers evaluate their experience less favorably following fellow customer's help. Human staff's and service robot's help resulted in similar service evaluation. Perceived role congruity is the underlying psychological mechanism. Instrumental help from firm representatives resulted in a more positive evaluation. Abstract: The key to excellent service delivery is to ensure harmonious interactions between service actors. Therefore, in the event of service failure incidents, an understanding of the roles and interactions of these service actors is critical to achieving positive service outcomes. This research addresses the question: How do interactions between customers and these service actors (human staff/automated technological interface/fellow customer) influence their service experience following a service failure? We draw on role theory and answer this question via three experimental studies. Findings show that customers evaluate their service experience less favourably when receiving service recovery from fellow customers rather than firms (human staff and service robots). Furthermore, a firm's instrumental recovery, rather than informational recovery, leads to a more favourable service evaluation, although this effect is absent when service recovery was given by fellow customers. Findings provide insights into the role of each actor in determining customer service evaluation.